LIVING VALUES EDUCATION PROGRAM SEBAGAI PEMBENTUK KARAKTER ANAK DI ERA MILENIAL - Nur Relawati Sarif; Rika Asmara Sejati; An-Nisa Apriani (Edusoshum : Journal of Islamic Education and Social Humanities, 2021)
Responding to the moral decline in the millennial generation as a result of advances in communication, information, and technology is a big challenge that must be faced together so that the formation of children's character needs to be instilled. The purpose of this research is to shape the character of the millennial generation through the living values ​​education program in the school environment. The research method used is library research with secondary data sources, namely research documents and supporting books. Data analysis in this study is content analysis. The results of the study indicate that the strength of character education and the participation of school educational institutions are the main foundations in providing motivation in the life of diversity. Character education becomes very important when the collapse of ethical values, morality, as a result of the progress of the times, especially in the millennial generation. By building character through the values ​​contained in the living values ​​education program, the millennial generation can have good character in accordance with the noble values ​​of the Indonesian nation.